ANALYSIS OF FLATWISE TENSILE STRENGTH TEST ON CARBON-FIBER WITH FIBERGLASS HONEYCOMB CORE SANDWICH COMPOSITE BASED ON ASTM C297 WITH VARIATIONS OF CORE CLEANING, CORE DRYING, AND BONDING METHODS - Octavinaldi Nurpratama, Taufik
The development of aircraft design and construction technology makes an increase in the need for material innovation. Currently, composite materials are widely used throughout the world in various fields due to their high strength and weight ratio, their resistance to corrosion, and the ease of fabrication for fabrication. The sandwich structure is an example of a composite material that has an interesting structural design concept, because with the selection of the right material and geometry, a construction that has a high stiffness to weight ratio can be achieved. Sandwich structures are generally used in structures where strength, stiffness and heavy efficiency are needed. To find out the strength of a sandwich structure needs to be tested, one of the test methods used is a flatwise tensile test. In this study, the authors varied the cleaning and drying methods of the core and the bonding method. These three variations are part of the specimen preparation process. This test requires five specimens for each configuration (variation), which later the specimen will be withdrawn until a failure occurs, whether it occurs inside the core, core to facing bond, or facing to block bond. The test results obtained show that the average tensile strength has increased when compared with the results of similar studies conducted by PT. Dirgantara Indonesia